2010
DOI: 10.1108/17538271011027087
|View full text |Cite
|
Sign up to set email alerts
|

The impact of buyer‐type on house price

Abstract: Purpose -This paper aims to report the results of a study conducted to determine whether investors systematically pay less for single-family houses than do buyer/residents. Design/methodology/approach -Data from 3,443 single-family house transactions were subjected to regression analysis. Findings -Investors in this study paid 13.24 percent less, on average, than buyers who reside in the property.Research limitations/implications -The study was limited to transactions occurring during a single year in one Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…However, the speculation is qualified through the number of confirmer transaction as the transaction will be increased itself from time to time. Active speculation in the market will direct increase the price of housing in the area due to the expectation of the investor in this market (Larsen, 2010). But it will also lead to price boom and bubble in this area.…”
Section: Housing Speculationmentioning
confidence: 99%
“…However, the speculation is qualified through the number of confirmer transaction as the transaction will be increased itself from time to time. Active speculation in the market will direct increase the price of housing in the area due to the expectation of the investor in this market (Larsen, 2010). But it will also lead to price boom and bubble in this area.…”
Section: Housing Speculationmentioning
confidence: 99%
“…The study revealed that different building types have different critical factors influencing their rental values within different residential densities (Adegoke, 2014). Blair and Larsen (2010) Nilsson et al (2006); Woolley et al (2008) and Kleinhans (2009) on the importance of social relationships among residents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Subsequently, they recommended that for residential properties to command competitive rental values, amenities likewall-fence and windows with burglar proof amongothers should be provided (Olujimi & Bello, 2009). Larsen (2010) reported on a study to determine whether investors pay less for single-family houses than do buyer/residents. This was done by subjecting transactional data from 3,443 single-family houses to regression analysis and it was confirmed that on average investors systematically pay 13.23 per cent less than those residing in the houses (Larsen, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations